Pairs‐trading and spread persistence in the European stock market. Issue 9 (28th May 2018) - Figuerola‐Ferretti, Isabel; Paraskevopoulos, Ioannis; Tang, Tao
Abstract : In this paper, we adapt the demand and supply framework introduced by Figuerola‐Ferretti and Gonzalo ( Journal of Econometrics, 2010) to illustrate the dynamics of Pairs‐trading. We underline the process by which a finite elasticity of demand for spread trading determines the speed of mean reversion and pairs‐trading profitability. A persistence‐dependent trading trigger is introduced accordingly. Applied to STOXX Europe 600–traded equities, our strategy exploits price leadership for portfolio replication purposes and delivers Sharpe ratios that outperform the benchmark rules used in the literature. Portfolio performance and mean reversion are enhanced after firm fundamental factor restrictions are imposed.